Asymmetric growth and inflation developments in the acceding countries: a new assessment - Stefaan Ide; Philippe Moës (National Bank of Belgium, 2004)
In this paper, we use a SVAR model in order to study the asymmetry of growth and inflation developments in the acceding countries vis-à-vis the euro area over the years 1995-2003. The model combines two strands of the literature, the explanation in terms of country-specific and euro area shocks, and a further split between supply and demand shocks. The four structural shocks may all create asymmetries vis-à-vis the euro area. It appears that country-specific shocks are the main source of growth or inflation divergence, rather than the distinct way in which acceding countries react to euro area shocks. But whereas country-specific supply shocks are mainly responsible for growth divergence, country-specific demand shocks are mainly responsible for inflation asymmetry. Hence, a low asymmetry in terms of growth does not necessarily imply a low asymmetry in terms of inflation, although the latter is particularly important for countries aiming to join the euro area. There is some evidence that both asymmetries were on the fall over the last years of the sample.
Keywords: E3; F42; F15; C32; 330; optimal currency area; euro-area wide shocks vs. country-specific shocks; structural VAR.; Konjunkturzusammenhang; Optimaler Währungsraum; Inflation; Wirtschaftswachstum; Eurozone; VAR-Modell; Osteuropa